1989
DOI: 10.1109/43.24880
|View full text |Cite
|
Sign up to set email alerts
|

SIERRA: a 3-D device simulator for reliability modeling

Abstract: SIERRA is a 3-D general purpose semiconductor device simulation program which serves as a foundation for investigating integrated circuit (IC) device and reliability issues. This program solves the Poisson and continuity equations in silicon under dc, transient, and small-signal conditions. Executing on a vector/parallel minisupercomputer, SIERRA employs a matrix solver which uses an incomplete LU (ILU) preconditioned conjugate gradient square (CGS, BCG) method. The ILU-CGS method provides a good compromise be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Fully 3-D device simulators were first reported in the literature in the early 1980s [140], and some of the early work on 3-D device simulation was motivated by alpha-particle reliability issues [141], [142]. An early comparison of 2-D and 3-D charge-collection simulations showed that while the transient responses were qualitatively similar, significant quantitative differences existed, both in the magnitude of the current response and the time scale over which collection was observed [143].…”
Section: B Multidimensional Device Simulationsmentioning
confidence: 99%
“…Fully 3-D device simulators were first reported in the literature in the early 1980s [140], and some of the early work on 3-D device simulation was motivated by alpha-particle reliability issues [141], [142]. An early comparison of 2-D and 3-D charge-collection simulations showed that while the transient responses were qualitatively similar, significant quantitative differences existed, both in the magnitude of the current response and the time scale over which collection was observed [143].…”
Section: B Multidimensional Device Simulationsmentioning
confidence: 99%
“…The matrix calculation to obtain the potential solution is carried out by the ILU-CGS method. 12 The method is very fast and effective in solving an asymmetric matrix. The tolerance was set to 10 Ϫ8 .…”
Section: E Sequence Of the Simulatormentioning
confidence: 99%
“…It is interesting to compare the EMA with other algorithms which solve directly the linear system resulting from FD discretization. For such a comparison we have chosen the iterative CGS algorithm [14] which exhibits O(n 1.5 ) complexity in applications to band matrices resulting from FD discretization and has a low, O(n) memory requirements. Non-iterative methods of complexity O(n 1.5 ) also exist [13], but they tend to have bigger memory consumption.…”
Section: Performance Of the Edge Moving Algorithmmentioning
confidence: 99%